Gold Nanorod-Coated Hydrogel Brush Valves in Macroporous Silicon Membranes for NIR-Driven Localized Chemical Modulation - Nafis Mustakim; Youngsik Song; Sang-Woo Seo (Gels)
A two-dimensional array of microfluidic ports with remote-controlled valve actuation is of great interest for applications involving localized chemical stimulation. Herein, a macroporous silicon-based platform where each pore contains an independently controllable valve made from poly(N-isopropylacrylamide) (PNIPAM) brushes is proposed. These valves are coated with silica-encapsulated gold nanorods (GNRs) for NIR-actuated switching capability. The layer-by-layer (LBL) electrostatic deposition technique was used to attach the GNRs to the PNIPAM brushes. The deposition of GNRs was confirmed by dark-field optical microscopy, and the localized surface plasmon resonance (LSPR) of the deposited GNRs was analyzed using UV-Vis spectra. To evaluate the chemical release behaviors, fluorescein dye was employed as a model substance. The chemical release properties, like OFF-state diffusion through the valve, the ratio between ON-state and OFF-state chemical release, and the rapidness of chemical modulation of the valve, were investigated, varying the PNIPAM brush thickness. The results indicate that enhancing the thickness of the PNIPAM brush in our platform improves control over the chemical modulation properties. However, excessive increases in brush length may lead to entanglement, which negatively impacts the chemical modulation efficiency.